Hematopoietic Stem Cell Function and Survival Depend on c-Myc and N-Myc Activity - Laurenti, Elisa (2008)
Myc activity is emerging as a key element in acquisition and maintenance of stem cell properties. We have previously shown that c-Myc deficiency results in accumulation of defective hematopoietic stem cells (HSCs) due to niche-dependent differentiation defects. Here we report that immature HSCs coexpress c-myc and N-myc mRNA at similar levels. Although conditional deletion of N-myc in the bone marrow does not affect hematopoiesis, combined deficiency of c-Myc and N-Myc (dKO) results in pancytopenia and rapid lethality. Interestingly, proliferation of HSCs depends on both myc genes during homeostasis, but is c-Myc/N-Myc independent during bone marrow repair after injury. Strikingly, while most dKO hematopoietic cells undergo apoptosis, only self-renewing HSCs accumulate the cytotoxic molecule GranzymeB, normally employed by the innate immune system, thereby revealing an unexpected mechanism of stem cell apoptosis. Collectively, Myc activity (c-Myc and N-Myc) controls crucial aspects of HSC function including proliferation, differentiation, and survival.